National survey evaluating the provision of gastroenterology dietetic services in England. Issue 5 (16th June 2020) - Rej, Anupam; Buckle, Rachel Louise; Shaw, Christian Charles; Trott, Nick; Urwin, Heidi; McGough, Norma; Aziz, Imran; Sanders, David Surendran
Abstract : Aims: The aim of the study was to assess the provision of dietetic services for coeliac disease (CD), irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD). Methods: Hospitals within all National Health Service trusts in England were approached (n=209). A custom-designed web-based questionnaire was circulated via contact methods of email, post or telephone. Individuals/teams with knowledge of gastrointestinal (GI) dietetic services within their trust were invited to complete. Results: 76% of trusts (n=158) provided GI dietetic services, with responses received from 78% of these trusts (n=123). The median number of dietitians per 100 000 population was 3.64 (range 0.15–16.60), which differed significantly between regions (p=0.03). The most common individual consultation time for patients with CD, IBS and IBD was 15–30 min (43%, 44% and 54%, respectively). GI dietetic services were delivered both via individual and group counselling, with individual counselling being the more frequent delivery method available (93% individual vs 34% group). A significant proportion of trusts did not deliver any specialist dietetic clinics for CD, IBS and IBD (49% (n=60), 50% (n=61) and 72% (n=88), respectively). Conclusion: There is an inequity of GI dietetic services across England, with regional differences in the level of provision and extent of specialist care. Allocated time for clinics appears to be insufficient compared with time advocated in the literature. Group clinics are becoming a more common method of dietetic service delivery for CD and IBS. National guidance on GI dietetic service delivery is required to ensure equity of dietetic services across England.